A Study of the Impact and Reflection of Vision and Mission Statement on the Behaviour of Student Teachers with Respect to Institutional Climate of the Teacher Education Colleges - Pereira, Elvina Nevil (Journal of Advanced Research in Humanities and Social Sciences, 2023)
Institutional Climate is a vital factor in the overall achievement of an organization. It is an unwritten personality and the environment of a school which has an impact on its norms, value and expectations. To large extent vision and mission of the organization is reflected in the institutional climate. Colleges of teacher education work towards preparing effective teachers to meet the needs and confront the challenges of the diverse society. The present study is an attempt to study the Impact and Reflection of vision and mission statement on the Behaviour of Student Teachers with respect to Institutional Climate of the Teacher Education Colleges. Colleges of teacher education work towards helping the future teachers to recognize and utilize the knowledge that they possess in many ways in different settings the present study has taken into consideration the aspects of institutional climate such as Esprit, Communication and Transparency.